DIGITAL TRANSFORMATION AND ORGANIZATIONAL COMMUNICATION: A LITERATURE REVIEW OF MODELS, BARRIERS, AND OPPORTUNITIES - Joko S Dwi Raharjo (KENDALI: Economics and Social Humanities, 2025)
Digital transformation has become a major driving force that is fundamentally reshaping the business and organizational landscape. Successful implementation depends not only on technology adoption but also on an organization's ability to manage change, particularly through effective communication. This systematic literature review aims to deeply analyze the link between digital transformation and organizational communication, focusing on three key aspects: existing models, barriers encountered, and emerging opportunities. Using a systematic literature review (SLR) of 37 relevant journals published between 2018 and 2025, this study identified that organizational communication is a crucial element in various digital transformation models, serving as a mechanism for aligning visions, managing change, and building a digital culture. Key barriers identified include resistance to change, interdepartmental silos, and a lack of a clear communication strategy. On the other hand, digital transformation opens up opportunities to create more agile, transparent, and data-driven communication processes, which can ultimately improve collaboration and organizational performance. The review concludes that strategic integration of organizational communication is a critical success factor for digital transformation and provides recommendations for future research focused on developing adaptive communication frameworks in a digital context.